101 tees : restyle + refashion + revamp - Filian, Cathie, 1970- (Lark Crafts, 2011)
"Using super crafty techniques--from painting to dyeing, from iron-ons and patches to designing with cut, ripped, and torn elements--you'll be able to make totally cute tees that will be perfect for moms, teens, and everyone on your gift list! There's even a chapter of tees just for the guys, and another for making tees for holidays and special occasions."--P. [4] of cover.